Modus operandi for ethical action in social and health care in the era of digitalisation - Raija Koskinen; Kristiina Helminen; Arja Koski; Mikko Malkavaara; Päivi Sanerma; Päivi Sihvo (Finnish Social and Health Informatics Association, 2022)
The ethical operational model developed in SotePeda 24/7 project in 2018-2020 has since its launch been used in continuous learning in social and health care. The model was developed to work as a tool in identification of ethical issues in the digitising operational environment of social and health care, as well as to support ethical evaluation and decision-making. When the ethical operational model is embraced, it results into internalizing the reflective process of the model and increases the ability to face ethical dilemmas in the mode of modus operandi indicating socio-culturally established ways of engaging and of doing things. Our aim in this study is to evaluate the experiences gained of the implementation of the ethical operational model in continuous learning in social and health care. As research methods we apply qualitative evaluation: program theory-based and systems approach. As material of the study, we address the experiences gained from the practical use of the model. Additionally, we scrutinize the ethical operational model as an artefact, as co-constructed object, and make use of the multifaceted data from the time of developing the model. The results of our study indicate that when the ethical operational model has been systematically used in continuous learning, the experiences have been overall positive, increasing awareness and ethical competence of the participants. From the point of view of its systemic impact, the scrutiny of the ethical operational model as an artefact, indicates that the focal constituents embedded enable even those new to the model to engage in it and to develop the content further via reflection. We conclude that the ethical operational model has found its way in active use as means of continuous learning in social and health care. The model may gradually become infused in digital era practices and be vitally present in action as modus operandi.